2021
DOI: 10.1038/s41598-021-87978-2
|View full text |Cite
|
Sign up to set email alerts
|

Knee loading in OA subjects is correlated to flexion and adduction moments and to contact point locations

Abstract: This study evaluated the association of contact point locations with the knee medial and lateral contact force (Fmed, Flat) alterations in OA and healthy subjects. A musculoskeletal model of the lower limb with subject-specific tibiofemoral contact point trajectories was used to estimate the Fmed and Flat in ten healthy and twelve OA subjects during treadmill gait. Regression analyses were performed to evaluate the correlation of the contact point locations, knee adduction moment (KAM), knee flexion moment (KF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
3
12
0
1
Order By: Relevance
“…It is well known that biomechanical factors such as excessive or frequent loading, misplaced contact regions, and altered muscle loading are associated with impaired medial-to-lateral load distribution and correlates with regional cartilage changes in KOA. Our findings were supported by previous studies that the overall condition of the cartilage in the M-A compartment of the tibial plateau was worse than in the L-A region of the tibial plateau. Thus, this may indicate that the cartilage degeneration expands from the anterior to the posterior in the medial tibial plateau to the lateral tibial plateau.…”
Section: Resultssupporting
confidence: 84%
“…It is well known that biomechanical factors such as excessive or frequent loading, misplaced contact regions, and altered muscle loading are associated with impaired medial-to-lateral load distribution and correlates with regional cartilage changes in KOA. Our findings were supported by previous studies that the overall condition of the cartilage in the M-A compartment of the tibial plateau was worse than in the L-A region of the tibial plateau. Thus, this may indicate that the cartilage degeneration expands from the anterior to the posterior in the medial tibial plateau to the lateral tibial plateau.…”
Section: Resultssupporting
confidence: 84%
“…The effect of gait modifications on latKCF has not been investigated in the past. Previous studies found KFM or KEM as the main contributor to latKCF 41 , suggesting that offloading gait should target these parameters. 36 , 39 However, this presumption need to be validated in an experimental study.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of gait modi cations on latKCF has not been investigated in the past. Previous studies found KFM or KEM as the main contributor to latKCF 35 , suggesting that o oading gait should target these parameters. 31,33 All four statistical models from the present study revealed a negatively directed correlation between KAM and latKCF.…”
Section: Discussionmentioning
confidence: 95%